Creative and Intuitive Decision-Making Processes: A Comparison of Brazilian and German Soccer Coaches and Players. Issue 4 (2nd October 2019) - Klatt, Stefanie; Noël, Benjamin; Musculus, Lisa; Werner, Karsten; Laborde, Sylvain; Lopes, Mariana Calábria; Greco, Pablo J.; Memmert, Daniel; Raab, Markus
ABSTRACT: Purpose : The concepts of creativity and intuition have been well studied in isolation, but less is known about their distinctive contributions to option generation in decision making. Method : We examined the relation between creative and intuitive decision making in two studies—one involving coaches and one involving soccer players—using video footage of real soccer matches. Additionally, we analyzed whether this relation is culture generic or culture specific by conducting matched cross-cultural studies in a European and a South American country. Results : In Study 1, results indicate a conceptual overlap of creativity and intuition for Brazilian and German soccer coaches. Furthermore, coaches did not differ in their evaluation of creative and intuitive actions of players of both cultures. In Study 2, we found that for both subsamples the total number of generated options was positively correlated with the quality of the first and the final option and that the quality of players' first (intuitive) option was higher than that of options generated later. Moreover, results indicate a positive correlation between a player's creativity score and the quality of the first generated option for the whole sample. Conclusion : Overall, our findings provide meaningful information regarding athletes' and coaches' option-generation processes in decision making in complex team sports.